SEEING BEYOND WORDS: METAFUNCTIONS ANALYSIS OF EFL TEXTBOOKS - Darong, Hieronimus Canggung (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2023)
This study carefully applies Systemic Functional Linguistics (SFL) to identify common linguistic patterns to examine English as a Foreign Language (EFL) textbooks. This descriptive qualitative study addresses the ideational, interpersonal, and textual metafunctions of English as a Foreign Language (EFL) textbooks as the research focus. The frequent use of material process, particular nominal group types such as Thing (T) and Numerative Thing (NT), the nuanced modality conveyed by "should," "would," and "will," and the use of narrative perspectives with third-person singular pronouns ("he" and "she") are noteworthy among these patterns. The identified linguistic features furnish invaluable pedagogical insights for the stakeholders of English learners, including the teachers, and provide guidance for targeted language instruction. Furthermore, these results are also invaluable for material development since the study highlights the importance of integrating SFL principles within the classroom discourse. The study also emphasizes the significance of SFL-based textbooks as learning facilitates. The study discovers that SFL-based textbook analysis provides well-informed instruction, allowing teachers to modify their teaching methods to meet students' communicative needs better. Despite limitations, the analysis remains a valuable tool in the classroom discourse as it better portrays the foreign language classroom discourse.